2020
DOI: 10.7759/cureus.9278
|View full text |Cite
|
Sign up to set email alerts
|

Large Vessel Occlusion Stroke Secondary to Acute Aortic Dissection

Abstract: Aortic dissection carries a high mortality of up to 40% at the time of initial dissection and an additional 1% per hour the dissection is untreated. Patients with acute aortic dissection most commonly present with chest or back pain. Less frequently, it manifests without pain with predominant neurologic symptoms secondary to an acute stroke. We present the case of a 53year-old male presenting with acute onset aphasia and right-sided weakness. Incidentally, CT angiography of his neck revealed a carotid artery d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 17 publications
0
2
0
1
Order By: Relevance
“…Nur ein Patient hatte dabei eine AD-B, zwei Patienten stellten sich mit einer chronischen Aortendissektion vor. Das Vorliegen einer AD-A sowie eines proximalen zerebralen Gefäßverschlusses bleibt weiterhin eine individuelle Entscheidung unter Mitbeurteilung aller Fachgebiete [38].…”
Section: Symptomatikunclassified
“…Nur ein Patient hatte dabei eine AD-B, zwei Patienten stellten sich mit einer chronischen Aortendissektion vor. Das Vorliegen einer AD-A sowie eines proximalen zerebralen Gefäßverschlusses bleibt weiterhin eine individuelle Entscheidung unter Mitbeurteilung aller Fachgebiete [38].…”
Section: Symptomatikunclassified
“…Unexpected aortic arch lesions have been observed in several previous studies. However, previous studies have mainly focused on the aortic arch abnormalities revealed using computed tomography (CT) [ 14 , 15 , 16 , 17 ]. It is not difficult to identify aortic arch abnormalities on neck CT angiography if the scan range is appropriate as the CT modality delivers clear and specific information.…”
Section: Introductionmentioning
confidence: 99%
“…Untreated mortality of AAAD has been reported to be approximately 1% to 2% per hour after symptom onset, with up to 90% of patients succumbing within two weeks. However, very few studies have looked at the sex difference of AAAD [Rawla 2019;Pawlukiewicz 2020]. Although the International Registry of Acute Aortic Dissection (IRAD) reported sex-related differences in acute aortic dissection, these data did not necessarily reflect the status of the general population due to different races, medical insurance, and socio-cultural backgrounds [Evangelista 2016;Tsai 2009;Berretta 2016].…”
Section: Introductionmentioning
confidence: 99%